Unique 1D/2D Bi2O2CO3 nanorod-Bi2WO6 nanosheet heterostructure: synthesis and photocatalytic performance. Issue 35 (11th August 2021) - Qian, Hao-Zhi; Wang, Bo; Liu, Meng-Ting; Zhao, Nan-Nan; Wang, Zheng-Hua; Peng, Yin
Abstract : A novel 1D/2D Bi2 O2 CO3 –Bi2 WO6 heterostructure was synthesized by high temperature calcination. These 1D/2D Bi2 O2 CO3 –Bi2 WO6 heterostructures displayed an outstanding photocatalytic activity to degrade organic compounds. Abstract : A novel 1D/2D Bi2 O2 CO3 –Bi2 WO6 heterostructure with a high quality interface was synthesized by high temperature calcination of Bi (OHC2 O4 )·2H2 O/Bi2 WO6 precursors in CO2 . Bi2 WO6 nanosheets were grown vertically on porous Bi2 O2 CO3 rods by epitaxial growth. The 1D/2D Bi2 O2 CO3 –Bi2 WO6 heterostructures display high photocatalytic activity to degrade salicylic acid, phenol and rhodamine B. This enhanced photocatalytic activity was attributed to the synergistic effects of the unique 1D/2D heterostructure and the formation of a high-quality interface between Bi2 O2 CO3 and Bi2 WO6 . Radical scavenger experiments proved that ˙O2 − and photogenerated holes played key roles during the photodegradation process. A simple and general route is offered in this study to synthesize 1D/2D heterostructures with excellent photocatalytic performance.